2018
DOI: 10.1002/ejic.201801039
|View full text |Cite
|
Sign up to set email alerts
|

Gd‐Based Mesoporous Silica Nanoparticles as MRI Probes

Abstract: Over the last decade, a number of Gd III chelates and paramagnetic ions were conjugated or included into mesoporous silica nanoparticles (MSNs) and tested as potential magnetic resonance imaging (MRI) and theranostic probes. These systems can concentrate a large payload of paramagnetic sites in the region where they localize, thus increasing the sensitivity of the technique. In addition, when attached to the silica surface, the Gd III complexes reduce their rotational tumbling motion, which leads to an improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 113 publications
0
43
0
Order By: Relevance
“…Recently, Carniato et al summarised the most remarkable examples of Gd-based mesoporous silica nanoparticles for MRI. In this work, the influence over the relaxometric properties of important factors such as the porosity, the localisation of the paramagnetic chelate and the surface properties of the mesoporous silica nanoparticles are discussed in detail [45]. For instance, Davis et al reported mesoporous silica nanoparticles doped with Gd in the inner or outer part of the pore and in the surface of the particle showing great differences in the relaxivity values depending on the Gd localisation [46].…”
Section: Silica Based Nanoparticlesmentioning
confidence: 97%
“…Recently, Carniato et al summarised the most remarkable examples of Gd-based mesoporous silica nanoparticles for MRI. In this work, the influence over the relaxometric properties of important factors such as the porosity, the localisation of the paramagnetic chelate and the surface properties of the mesoporous silica nanoparticles are discussed in detail [45]. For instance, Davis et al reported mesoporous silica nanoparticles doped with Gd in the inner or outer part of the pore and in the surface of the particle showing great differences in the relaxivity values depending on the Gd localisation [46].…”
Section: Silica Based Nanoparticlesmentioning
confidence: 97%
“… Irrespective of the functionalization methods, with the choice of organosilanes, the charge, hydrophobicity and textural properties of silica can be tailored. Thus, selecting a right organosilane is very important In comparison, co‐condensation offers the homogeneous distribution of functional groups in high loading on silica. Maintaining pH is important during the functionalization of silica by co‐condensation as it has the influence on the rate of condensation and size of silica particles …”
Section: Methods Of Silica Functionalizationmentioning
confidence: 99%
“…: sol‐gel method) undergoes effective functionalization as it has more silanol groups. The ability of different silanol groups to undergo functionalization is in the following order: hydrogen bonded silanols>geminal silanols>isolated silanols. Locating three neighbouring surface silanols close enough to bond with the same silane is very difficult due to the steric and strain effects. Hence, mono and bi‐podal anchoring of functional groups seem to be more realistic. While preparing functionalized mesoporous silicas (especially through co‐condensation), size and concentration of organosilanes are the key factors influencing the fundamental porous structure of mesoporous silicas …”
Section: Methods Of Silica Functionalizationmentioning
confidence: 99%
“…The paramagnetic nanoparticles proposed in the literature are composed using a diamagnetic inorganic support functionalized with Gd(III)-chelates, opportunely modified to promote their chemical attachment on the surface [5][6][7][8][9][10]; or they are completely inorganic [11,12]. In the last case, the particles contain directly in the framework paramagnetic Gd 3+ ions, often combined with other lanthanides with specific properties [11].…”
Section: Introductionmentioning
confidence: 99%